Religious Harmony in Islamic Concept and its Historic Practices: Freedom of Religion and Pluralism as the Basis - Sukron Kamil (Sunan Kalijaga: International Journal of Islamic Civilization, 2022)
Religion, at least in the practice in history, even as the concept understood by some of the adherents has the power of uniting and disuniting. Even so, conceptually as proven in most of its historical practices, harmony in Islam is emphasized both internally among Muslims and between Muslims with the adherents of other religions. Among Muslims, harmony can be seen from the concept of ikhtilâf and ukhuwwah Islâmiyyah, while the harmony with adherents of other religions can be seen from the freedom of religion and pluralism as the basis. From the view of the Qur’an, pluralism or religious diversity is sunnatullah (law of nature); the emphasis in Islam on inter religious dialogs is for the purpose of knowing one another, communicate and cooperation (civic pluralism); and also, the view of theological pluralism, where in Islam there are many Islamic scholars who acknowledge salvation (the possibility of entering heaven) to adherents of other religions. However, keeping in mind that theological pluralism is denied by the majority of Islamic scholars, then inter-religious harmony is more probable to be based on civic pluralism and freedom of religion. In Islam, not only freedom of religion is acknowledged but the freedom to be atheist is also acknowledged as long as it doesn’t create chaos; non-recognition of death penalty for apostates by some scholars; the basis of the syari’a in Islam is the general benefit (public); and the acknowledgement of the same political and economic rights among Muslims and non-Muslims.